Rekabentuk pembelajaran bagi meningkatkan tahap kefahaman konsep pelajar dalam tajuk Trigonometri menggunakan perisian sumber terbuka Geogebra - Suhaimin, Suza Hamira (2014)
This research aims to develop leaning instructions using open source mathematical software of GeoGebra (simple called as RP-GGB). The RP-GGB was developed to assist secondary school student to improve their conceptual understanding in Trigonometry. This study was adopted ADDIE model whilst the research activities were carried out in four phase namely Phase I, Phase II and Phase III, Phase IV and Phase V. This study was conducted in Single Quasi Experiment. In Phase I, a series of analyses of student’s learning difficulties in Trigonometry were conducted to provide essential baseline information required for the design and development of RP-GGB. In Phase II and Phase III, the design and development of RP-GGB were performed involving determination of structure, content and scope of learning instructions as well as the formulation of learning activities that would help easing students’ learning difficulties as we as improving their conceptual understanding in Trigonometry. The visualization of feature GeoGebra has been capitalized for these purposes. In Phase IV, the RP-GGB was tried out to a group twenty-two of form 4 students selected from a school in the state of Selangor. In Phase V, the effectiveness of RP-GGB in assisting students to improve their conceptual understanding in Trigonometry was conducted. The level of students’ conceptual understanding in Trigonometry before and after the use of RP-GGB were measured by specially designed Trigonometry Test. The test score were generated using rubrics. The data analyzed using simple statistical approach involving comparison of scores, the changes of scores and graphical plots of score before and after the use of RP-GGB. The study was found evidences suggesting that the RP-GGB has been effective in assisting students to improve their conceptual understanding in Trigonometry. The study thus provides a practical alternative of learning to assist students for ease their learning difficulties as well as improving their conceptual understanding in Trigonometry.